Deformation Behaviour Of Metallic Cellular Structure Using Finite Element Analysis - Ahmad, Musa (Universiti Sains Malaysia, 2022)
The deformation of a metallic cellular structure (honeycomb) due to uniaxial compression in x, y and z- directions is investigated in this study. The honeycomb model is an engineering structure that is widely used nowadays. The material that was used is Aluminium 7075.The honeycomb model is used as a structure by attaching it with the panel or sandwich panel. Since honeycomb consists of porosity characteristic, the force reaction and specific energy absorption is being focused in this project. The specific energy absorption of the cellular structure is influenced by its porosity, pore size and strain rate. The pore size differs due to the length of the honeycomb. In this study, the cell wall thickness is varied from 0.25mm to 1.00mm. To change the porosity size, the honeycomb model has two different lengths at 10mm and 15mm. The strain rate will affect the force reaction and the SEA of the honeycomb. It is because the strain rate will cause the change of modulus and the yield strength. As a result, the increasing strain rate produce high force reaction against the deformation. The increase of cell length (cell size) does decrease the SEA and the thicker thickness of the honeycomb model (cell wall) does increase the SEA. However, some honeycomb models at higher strain rate exhibits a different result.